Atrial fibrillation and risk of progressive heart failure in patients with preserved ejection fraction heart failure. (4th July 2022) - Gierula, John; Cole, Charlotte A.; Drozd, Michael; Lowry, Judith E.; Straw, Sam; Slater, Thomas A.; Paton, Maria F.; Byrom, Rowenna J.; Garland, Ellis; Halliday, Georgia; Winsor, Sarah; Lyall, Gemma K.; et al.
Abstract: Aims: Understanding of the pathophysiology of progressive heart failure (HF) in patients with heart failure with preserved ejection fraction (HFpEF) is incomplete. We sought to identify factors differentially associated with risk of progressive HF death and hospitalization in patients with HFpEF compared with patients with HF and reduced ejection fraction (HFrEF). Methods and results: Prospective cohort study of patients newly referred to secondary care with suspicion of HF, based on symptoms and signs of HF and elevated natriuretic peptides (NP), followed up for a minimum of 6 years. HFpEF and HFrEF were diagnosed according to the 2016 European Society of Cardiology guidelines. Of 960 patients referred, 467 had HFpEF (49%), 311 had HFrEF (32%), and 182 (19%) had neither. Atrial fibrillation (AF) was found in 37% of patients with HFpEF and 34% with HFrEF. During 6 years follow‐up, 19% of HFrEF and 14% of HFpEF patients were hospitalized or died due to progressive HF, hazard ratio (HR) 0.67 (95% CI: 0.47–0.96; P = 0.028). AF was the only marker that was differentially associated with progressive HF death or hospitalization in patients with HFpEF HR 2.58 (95% CI: 1.59–4.21; P < 0.001) versus HFrEF HR 1.11 (95% CI: 0.65–1.89; P = 0.7). Conclusions: De novo patients diagnosed with HFrEF have greater risk of death or hospitalization due to progressive HF than patients with HFpEF. AF is associated with increased risk of progressive HF death or hospitalization in HFpEF but not HFrEF, raising the intriguing possibility that this may be a novel therapeutic target in this growing population.